PRODUKSI UBI JALAR (Ipomea batatas L.) KARENA PENGARUH KETINGGIAN BEDENGAN DAN JENIS MULSA - Kasifah, Kasifah; Mado, Irwan; Sam, Jumrah Aspiani; Pudji, Nusron Petta (Percetakan Umi Toaha Makassar, 2024)
Sweet potato plants require bed height and type of mulch for good growth and production. This research aims to determine the effect of bed height and mulch type on sweet potato (Ipomoea batatas L.) production. The study used a factorial randomized block design (RBD) with 2 factors. The first factor is the treatment of bed height and the second is the mulch type. The research was analyzed using analysis of variance and continued with an honest significant difference (HSD) test which will be done using the Excel application. The research showed that bed height and partial use of mulch significantly affected tuber production in sweet potatoes. The best bed height is 30 cm. The use of silver-black plastic mulch has a significant influence on sweet potato production. The interaction between bed height and mulch type only significantly affected tuber length in sweet potatoes